2006
DOI: 10.1016/j.nepr.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Measures that can be used to instill critical thinking skills in nurse prescribers

Abstract: Critical thinking is a pervasive skill that involves scrutinizing, differentiating, and appraising information and reflecting on the information gained in order to make judgements and inform clinical decisions. Studies inform us of the need for agreement on the approaches used to teach and measure critical thinking. Nurse prescribers undertake an advanced role that encompass the need to be able to make clinically based decisions about the appropriateness of a specific medication. This requires critical thinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Adams et al (1999) indicated increasing critical thinking levels with the increasing years of experience in nursing profession. Banning (2006) found that only two out of 37 nurses were able to use of critical thinking in clinical decision making but others were quite limited in using critical thinking abilities. These findings are similar to current findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adams et al (1999) indicated increasing critical thinking levels with the increasing years of experience in nursing profession. Banning (2006) found that only two out of 37 nurses were able to use of critical thinking in clinical decision making but others were quite limited in using critical thinking abilities. These findings are similar to current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses with these features can establish cause-effect relationships. Professional career, autonomy and power affect the nurses positively (Banning, 2006;Riddell, 2007). The quality of nursing care depends on integration of critical thinking skills with implementation environment.…”
Section: Introductionmentioning
confidence: 99%
“…suggest use of higher level objectives incorporating analysing, evaluating & creating. Interestingly, faculty used many lower level objectives (remembering, understanding & applying) but used multiple active, reflective, and cooperative strategies which are known to promote CT (Banning 2006;Loving & Wilson 2000;Simpson & Courtney 2002). Despite the use of lower level objectives, the students were actively engaged in their learning.…”
Section: Discussionmentioning
confidence: 99%
“…Second, nursing education scholars were evaluating and assessing the ways in which concept maps functioned as a learning strategy (Abel & Freeze, 2006;August-Brady, 2005;Banning, 2006;Bowles, 2006;Brunt, 2005;Chabeli, 2010;Clayton, 2006;Ellermann, Kataoka-Yahior, & Wong, 2006;Fonteyn, 2007;Garrett, 2005;Gul & Bowman, 2006;Harpaz, Balik, & Ehrenfeld, 2004;Hay, 2007;Hicks-Moore, 2005;Hicks-Moore & Pastirik, 2006;Hill, 2006;Hsu, 2004;Hsu & Hsieh, 2005;Johns, 2003;Kinchin & Hay, 2005;King & Shell, 2002;Laight, 2006;Latini, 2009;Luckowski, 2003;Pardue, Tagliaren, Valiga, Davison-Price, & Orehowsky, 2005;Pilcher, 2009;Senita, 2008;Staib, 2003;Vacek, 2009;Veo, 2010;Walsh & Seldomridge, 2006;Wheeler & Collins, 2003). This body of work looked at concept maps as a strategy to promote meaningful learning, a method for collaborative learning, a strategy to promote higher level thinking, critical thinking and clinical decision making, and a methodology for fostering the linkages between theory and practice in a clinical setting.…”
Section: Expansion and Adaptation (2000-2010)mentioning
confidence: 99%
“…The use of concept maps was studied in critical care (Dobbin, 2001;Hart, 2000), staff development (Phelps et al, 2009;Zimmerman & Pilcher, 2008;), RN education (Speziale, & Jacobson, 2004), continuing education programs for nurse prescribers (Banning, 2006), the operating department (Sewchuk, 2005), graduate student learning (Giddens, 2006), online courses (Conceição & Taylor, 2007;Ertmer & Nour, 2007), new graduate transition programs (Bratt, 2009;St. Cyr & All, 2009;Wilgis & McConnell, 2008), and neonatal intensive care (Zimmerman & Pilcher, 2008).…”
Section: Expansion and Adaptation (2000-2010)mentioning
confidence: 99%